The Effects of Clinorotation on the Host Plant, Medicago truncatula, and Its Microbial Symbionts - Dauzart, Ariel J. C.; Vandenbrink, Joshua P.; Kiss, John Z. (Frontiers in Astronomy and Space Sciences, 2016)
Understanding the outcome of the plant-microbe symbiosis in altered gravity is vital to developing life support systems for long-distance space travel and colonization of other planets. Thus, the aim of this research was to understand mutualistic relationships between plants and endophytic microbes under the influence of altered gravity. This project utilized the model tripartite relationship among Medicago truncatula ¬– Sinorhizobium meliloti – Rhizophagus irregularis. Plants were inoculated with rhizobial bacteria (S. meliloti), arbuscular mycorrhizal fungi (R. irregularis), or both microbes, and placed on a rotating clinostat. Vertical and horizontal static controls were also performed. Clinorotation significantly reduced M. truncatula dry mass and fresh mass compared to the static controls. The addition of rhizobia treatments under clinorotation also altered total root length and root-to-shoot fresh mass ratio. Nodule size decreased under rhizobia + clinorotation treatment, and nodule density was significantly decreased compared to the vertical treatment. However, inoculation with arbuscular mycorrhizal fungi was shown to increase biomass accumulation and nodule size. Thus, clinorotation significantly affected M. truncatula and its symbiotic relationships with S. meliloti and R. irregularis. In the long term, the results observed in this clinostat study on the changes of plant-microbe mutualism need to be investigated in spaceflight experiments. Thus, careful consideration of the symbiotic microbes of plants should be included in the design of bioregenerative life support systems needed for space travel.